2015
DOI: 10.1016/j.chb.2015.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Motivation matters: Interactions between achievement goals and agent scaffolding for self-regulated learning within an intelligent tutoring system

Abstract: a b s t r a c tIn this study, we examined the influence of achievement goals and scaffolding on self-regulated learning (SRL) and achievement within MetaTutor, a multi-agent intelligent tutoring system. Eighty-three (N = 83) undergraduate students were randomly assigned to either a control or prompt and feedback condition and engaged in a 1-h learning session with MetaTutor to learn about the human circulatory system. Process and product data were collected from all participants prior to, during, and following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
1
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 71 publications
6
120
1
11
Order By: Relevance
“…Biliş üstünün kritik bir bileşeni olarak görülen yansıtmanın, öğrencilerin daha iyi anlamasını sağladığı (Slavin, 1996;Gama, 2004;Stark ve Krause, 2009), biliş üstü beceri gelişimine destek olduğu (Martin-Kniep, 2000;Gama, 2004;Duffy ve Azevedo, 2015), öğrenme verimliliğini artırdığı (Martin-Kniep, 2000;Gama, 2004;Bannert vd., 2015), üst düzey düşünme becerisi kazandırdığı (Hmelo ve Ferrari, 1997;Hadwin ve Webster, 2013) ve öğrenciyi kendini geliştirmeye yönlendirdiği vurgulanmaktadır (Moon, 1999, s.99). Yansıtma etkinliklerinden biri olan yansıtıcı soruların da bireylerin kendi öğrenme sürecini planlama, izleme (Lin vd., 1999;Lin, 2001) ve değerlendirme (Lin, vd., 1999) süreçlerini teşvik ettiği (Ge ve Land, 2003) ve öğrencilerin içsel geri bildirim vermelerini sağladığı (Berandi vd., 1995) bilinmektedir.…”
Section: Sonuç Ve öNerilerunclassified
“…Biliş üstünün kritik bir bileşeni olarak görülen yansıtmanın, öğrencilerin daha iyi anlamasını sağladığı (Slavin, 1996;Gama, 2004;Stark ve Krause, 2009), biliş üstü beceri gelişimine destek olduğu (Martin-Kniep, 2000;Gama, 2004;Duffy ve Azevedo, 2015), öğrenme verimliliğini artırdığı (Martin-Kniep, 2000;Gama, 2004;Bannert vd., 2015), üst düzey düşünme becerisi kazandırdığı (Hmelo ve Ferrari, 1997;Hadwin ve Webster, 2013) ve öğrenciyi kendini geliştirmeye yönlendirdiği vurgulanmaktadır (Moon, 1999, s.99). Yansıtma etkinliklerinden biri olan yansıtıcı soruların da bireylerin kendi öğrenme sürecini planlama, izleme (Lin vd., 1999;Lin, 2001) ve değerlendirme (Lin, vd., 1999) süreçlerini teşvik ettiği (Ge ve Land, 2003) ve öğrencilerin içsel geri bildirim vermelerini sağladığı (Berandi vd., 1995) bilinmektedir.…”
Section: Sonuç Ve öNerilerunclassified
“…Theories of self-regulated learning provide a useful lens to understand the inluence of selfinitiated management of thoughts, feelings and behaviours in achieving speciic learning goals in virtual learning communities [20,22]. Both cognitive receptivity to technological change and innovation and social learning collaborative styles relate to the use of self-regulatory strategies and responsiveness.…”
Section: Social Collaborative Learning and Cognitive Receptivity To Tmentioning
confidence: 99%
“…Collaborating with fellow students in a virtual learning seting through social tools, such as discussion forums, for example, requires self-initiated self-regulatory processes apart from the other-regulation processes represented by the social collaboration style preferences. However, research has shown that students often do not self-initiate a high degree of self-directed learning processes and often struggle when engaging in ill-structured learning tasks [22].…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…Examples of such studies can be found in the domain of classical educational studies, such as Wolters et al (2017) who find that students' self-perceptions of time management are associated with self-perceived motivational and strategic aspects of self-regulated learning. Time management is also investigated in LAbased studies applying trace data, such as in Duffy and Azevedo (2015), who find that learning time invested in self-regulated learning depends on the feedback mode students are put in. However, studies focussing on the timing of learning, rather than the time of learning, seem to be scarce: irrespective of how much time students learn, how do they regulate the timing of learning time, and what antecedents can explain these timing decisions?…”
Section: Self-regulated Learning and The Timing Of Learningmentioning
confidence: 99%